SISTEM PENGELOLAAN BADAN USAHA MILIK DESA (BUMDes) DALAM PEMBANGUNAN TAMBAK MILIK DESA (Studi Desa Lhok Euncien Kecamatan Baktiya Barat) - Sufi Sufi (Program Studi Administrasi Bisnis, 2021)
The village government of Lhok Euncien established BUMDes as a driving force for the economy in the village but in its management it has not been able to be managed efficiently. This is because the pond land which is the business asset of BUMDes is handed over to third parties due to limited capital, so that BUMDes managers cannot work effectively and efficiently as they should. This journal uses descriptive journals with qualitative methods. The results of the journal show that at the planning stage, they have purchased pond land as a BUMDes asset, but limited capital to manage so that it is handed over to a third party, the organizing stage has been carried out in a procedural manner, but does not function and goes according to plan. The mobilization stage is the lack of concern from the village government, BUMDes managers and the community towards the problems they face. And at the supervision stage, the BUMDes supervisor only supervises the annual report. Meanwhile, the obstacles faced are related to limited capital and the lack of human resources and public awareness of BUMDes business development.